2017
DOI: 10.1158/0008-5472.can-16-3403
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Scenes: Endo/Exocytosis in the Acquisition of Metastatic Traits

Abstract: Alterations of endo/exocytic proteins have long been associated with malignant transformation, and genes encoding membrane trafficking proteins have been identified as bona fide drivers of tumorigenesis. Focusing on the mechanisms underlying the impact of endo/exocytic proteins in cancer, a scenario emerges in which altered trafficking routes/networks appear to be preferentially involved in the acquisition of prometastatic traits. This involvement in metastasis frequently occurs through the integration of prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…This latter mechanism largely relies on the overexpression and amplification of genes that are involved in RTKs endocytosis and recycling, including several GTPases belonging to the Rab family which control vesicular trafficking (Caswell et al ., ; Cheng et al ., ; Frittoli et al ., ; Kajiho et al ., ; Wheeler et al ., ). Increased expression of endocytic/recycling molecules prolongs propagation of the signal and/or re‐locates RTKs and adhesive receptors at specific membrane sites, mainly involved in cancer cell invasion (Caswell et al ., ; Eppinga et al ., ; also reviewed in Lanzetti and Di Fiore, ; Mellman and Yarden, ; Mills et al ., ; Mosesson et al ., ; Sigismund et al ., ). Among these molecules, copy number gain and overexpression of the 5′‐inositol lipid phosphatase synaptojanin 2 ( SYNJ2 ) in breast cancer provides a paradigmatic example of sustained EGFR activation by altered trafficking pathways.…”
Section: Canonical Ligand‐dependent Egfr Signaling Pathwaymentioning
confidence: 97%
See 1 more Smart Citation
“…This latter mechanism largely relies on the overexpression and amplification of genes that are involved in RTKs endocytosis and recycling, including several GTPases belonging to the Rab family which control vesicular trafficking (Caswell et al ., ; Cheng et al ., ; Frittoli et al ., ; Kajiho et al ., ; Wheeler et al ., ). Increased expression of endocytic/recycling molecules prolongs propagation of the signal and/or re‐locates RTKs and adhesive receptors at specific membrane sites, mainly involved in cancer cell invasion (Caswell et al ., ; Eppinga et al ., ; also reviewed in Lanzetti and Di Fiore, ; Mellman and Yarden, ; Mills et al ., ; Mosesson et al ., ; Sigismund et al ., ). Among these molecules, copy number gain and overexpression of the 5′‐inositol lipid phosphatase synaptojanin 2 ( SYNJ2 ) in breast cancer provides a paradigmatic example of sustained EGFR activation by altered trafficking pathways.…”
Section: Canonical Ligand‐dependent Egfr Signaling Pathwaymentioning
confidence: 97%
“…In addition, through recycling, CME also serves to prolong EGFR signaling, a requirement critical to achieve a productive proliferative response, and to polarize EGFR signaling to specific regions of the PM (Bisi et al ., ; Sigismund et al ., ). Polarized trafficking of cargo proteins to regions of the PM represents one of the most frequently altered functions of endo/exocytosis in cancer as it is primarily involved in migration and invasion of metastatic cells and in maintenance of epithelial cell polarity (reviewed in Lanzetti and Di Fiore, ).…”
Section: Canonical Ligand‐dependent Egfr Signaling Pathwaymentioning
confidence: 99%
“…Solid tumors, initially triggered by oncogenic transformation, require numerous adaptations to progress to the aggressive metastatic state. Among these are alterations in receptor signaling and endocytic membrane trafficking that can lead to enhanced proliferation, survival, and invasive properties of the evolved cancer cell (Lanzetti and Di Fiore, 2017;Schmid, 2017). Previous studies have shown that p53 mutations linked to numerous cancers can alter endocytic trafficking of RTKs and integrins resulting in increased cell migration and metastasis (Muller et al, 2009;Muller et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Their signaling activities are, in turn, modulated by endocytic trafficking (Mellman and Yarden, 2013). Indeed, gain-of-function (GOF) p53 mutations, which contribute to a more invasive phenotype in multiple cancers (Lang et al, 2004;Olive et al, 2004) can trigger increased recycling of EGFR, cMET and b1 integrins (Lanzetti and Di Fiore, 2017;Muller et al, 2009;Muller et al, 2013). This, in turn, results in increased invasion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, defects of epithelial vesicle trafficking machinery are associated with impaired embryonic morphogenesis and tissue repair [2,3]. On the other hand, overactivation of this process can be responsible for the accelerated motility of cancer cells, driving tumor metastasis [11]. Therefore, elucidating vesicle trafficking mechanisms that regulate cell motility is fundamentally important for understanding the basic biology of epithelial barriers and the pathophysiology of tissue injury and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%